2012
DOI: 10.1093/jpids/pis012
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of 2 Dose Levels of a Thimerosal-Free Trivalent Seasonal Influenza Vaccine in Children Aged 6–35 Months: A Randomized, Controlled Trial

Abstract: Background.Improved influenza vaccine strategies for infants and preschool children are a high priority.Methods.The immunological response and safety of a thimerosal-free trivalent inactivated influenza vaccine at 2 different doses (0.50 mL vs 0.25 mL) was evaluated in children aged 6–35 months. The study was randomized, observer blind, multicenter, and stratified by age (6–23 months and 24–35 months), and it accounted for prior influenza immunization status.Results.Three hundred seventy-four children were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…[74]. A similar pattern, though less pronounced, was also observed with the H3N2 component [74]. The reasons for diminished immunogenicity of the Canadian vaccine are unknown although authors of the pediatric trial proposed more complete clearance of intact virus among other possible explanations.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…[74]. A similar pattern, though less pronounced, was also observed with the H3N2 component [74]. The reasons for diminished immunogenicity of the Canadian vaccine are unknown although authors of the pediatric trial proposed more complete clearance of intact virus among other possible explanations.…”
Section: Discussionmentioning
confidence: 69%
“…For example, in the pediatric trial including infants and toddlers 6-23 months of age similarly naïve to influenza as were our ferrets, the same schedule of two 0.5 mL doses of a thimerosal-free version of the 2008-09 Fluviral induced significantly lower H1N1 antibody responses than even half that volume (0.25 mL) per dose of Vaxigrip [74]. [74]. A similar pattern, though less pronounced, was also observed with the H3N2 component [74].…”
Section: Discussionmentioning
confidence: 80%
“…Practice regarding dose for young children varies around the world, with some jurisdictions routinely using a “half dose” for children up to 35 months of age and a 0.5 mL dose for older children. Public health in Canada first recommended the 0.5 mL dose for the 2011–2012 season [14]; recent evidence supports that this dose results in moderate improvement in antibody response without increase in reactogenicity [1516]. HI antibody responses in 6- to 35-month-olds were lower than in older children, but fulfilled CBER criteria [13] except for the SPR for the A/H3N2 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, studies have reported that increasing the ‘pediatric’ half-dose (0.25 ml) to the ‘adult’ full-dose (0.5 ml) may improve antibody responses in children aged 6–35 mo. In one randomized controlled study of TIV ( Flulaval™ ) in children 6–35 months, seroprotection rates in the full-dose group were 63.6–92.4%, and in the half-dose group were 53.4–84.7%, yet despite a modest increase in immune responses with the full- vs. half-dose, the GMTs were not significantly different 24 . Another study, which assessed full- and half-doses of TIV ( Vaxigrip ® , Sanofi-Pasteur), showed that although the seroprotection rate was 10% higher in the full- vs. half-dose group in children aged 6–11 months, and was superior for the A/H3N2 and B strain, superiority between the different dose groups was not shown in the overall population of children aged 6–23 months 14 .…”
Section: Discussionmentioning
confidence: 99%